(untitled) - Stuart, Timothy S. (San Francisco, 2003)
Children At Promise offers a breakthrough paradigm for raising healthy and responsible children who contribute positively to their world. School principal Dr. Tim Stuart and former teacher-of-the-year Cheryl Bostrom offer a practical book filled with illustrations that show how at-risk and advantaged children can realize their At Promise identity. Solidly grounded in tested educational and psychological theory as well as timeless biblical wisdom, Children At Promise provides parents and educators with the insights, motivation, and tools for raising successful children of P. R. O. M. I. S. E. character. AT PROMISE stands for A Adversity and pain can lead to growth T Trust between a caring adult and a child P Perseverance R Responsibility for our actions O Optimism M Motivated by identity I Integrity S Service E Engaged Play
Keywords: Problem children,Church work with problem children,Child rearing; Religious aspects,Christianity